A New Departure on Remote Island : A Case of Abalone Farming in Ehime, Japan - Kim, Jihoon; Nakayasu, Akira; Takenouchi, Naruhiho (KnE Life Sciences, 2016)
Japanese fish production is currently affected by two major currents: population ageing and lack of young leaders. I found a solution to resolve this problem which is the closed circulatory culture system on land. There is actual abalone farm that conducting these system in OH Island, Yahatahama City, Ehime Prefecture, Japan. Although there are many benefits of using this system, competitive price could be a problem. Abalone imports rapidly increased over decade and has encroached upon the abalone market in Japan. Therefore cost reduction is the most important task. Keywords: Remote Island, Abalone Farming, Grants-in-Aid Program